SISTEM INFORMASI PENCATATAN KEUANGAN PASAR PADA BADAN USAHA MILIK DESA (BUMDES) BERBASIS WEB MOBILE DI KANTOR DESA TARINGGUL TONGGOH KECAMATAN WANAYASA - Mulyana, Nanang; Dien TH, H.M. John; Faradila, Annita (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2023)
BUMDes are regulated in Article 1 paragraph (6) of the Minister of Home Affairs Regulation Number 39 of 2010, which states that BUMDes are village businesses formed or established by the village government where capital ownership and management are carried out by the village government and the community. The problem faced by the Taringgul Tonggoh Village BUMDes management is the weekly and monthly financial recording or bookkeeping process, BUMDes is still done manually. This Financial Recording Information System can help and facilitate BUMDes administrators in recording or financial bookkeeping. The process of recording or bookkeeping carried out by the management will be more effective and efficient. In this study using the waterfall method as a method of system development and modeling using Data Flow Diagrams (DFD). While making this program using the programming language Hypertext Preprocessor or Personal Home Page (PHP). The results of this study are to produce an information system that makes it easier for BUMDes administrators to carry out the process of recording or financial accounting using the Mobile Web-Based Village-Owned Enterprises (BUMDes) Financial Recording Information System in Taringgul Tonggoh Village, Wanayasa District. PHP is a programming language that is commonly used in creating and developing a website. The function of PHP in general is to change static page sites into dynamic pages. So web pages can adjust the appearance of content based on the situation so it doesn't just look like that. The advantages of using the PHP programming language include: Easy to learn, many uses, cost-effective, Integrated with databases.